2018
DOI: 10.1111/cea.13101
|View full text |Cite
|
Sign up to set email alerts
|

Component‐resolved diagnostics demonstrates that most peanut‐allergic individuals could potentially introduce tree nuts to their diet

Abstract: PR-10-sensitizations were frequent and strong regardless of peanut allergy status. Component-resolved diagnostics can be employed to demonstrate to patients that sensitization to seed storage proteins of tree nuts is uncommon. Several tree nuts could potentially be reintroduced to the diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 36 publications
2
41
0
Order By: Relevance
“…8,13,14,23,52 The differentiation between clinical cross-reactivity (co-allergy) and serologic crossreactivity in the absence of clinically manifest co-allergy is a wellknown diagnostic challenge in food allergy to peanut, tree nuts, and other seeds. 14,23,52 Molecular cross-reactivity relies on the presence of conserved epitope structures of proteins and is hence observed in general among closely related members of the same protein family. 29,53 We observed a moderate correlation 54 between the 2S albumins Cor a 14 and Jug r 1 from walnut ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…8,13,14,23,52 The differentiation between clinical cross-reactivity (co-allergy) and serologic crossreactivity in the absence of clinically manifest co-allergy is a wellknown diagnostic challenge in food allergy to peanut, tree nuts, and other seeds. 14,23,52 Molecular cross-reactivity relies on the presence of conserved epitope structures of proteins and is hence observed in general among closely related members of the same protein family. 29,53 We observed a moderate correlation 54 between the 2S albumins Cor a 14 and Jug r 1 from walnut ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research is available describing patients with a high probability of reactivity to peanut showing either mono-sensitization to Ara h 2 or sensitization to both Ara h 2 and h 6, however there is little research describing mono-sensitization to Ara h 6 alone. 9,10 Due to its similarity to Ara h 2 in that they are both 2S albumins, Ara h 6 is also a component that has a high probability of reactivity with exposure. It is important to note that the Ara h 6 component is not found on routine component testing.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of IgE against 2S albumins in cashew (Ana o 3), walnut (Jug r 1) and hazelnut (Cor a 14) were correlated with patients experiencing GI reactions, which correspond well with the digestion‐resistant characteristics of 2S albumins . Additionally, component‐resolved diagnostics for peanut‐allergic subjects recently showed that sensitization to seed storage proteins in tree nuts was uncommon, suggesting that many peanut‐allergic patients could tolerate tree nuts without reactions …”
Section: Allergen Biochemistrymentioning
confidence: 99%
“…29 Additionally, component-resolved diagnostics for peanut-allergic subjects recently showed that sensitization to seed storage proteins in tree nuts was uncommon, suggesting that many peanut-allergic patients could tolerate tree nuts without reactions. 30…”
Section: Allergen Biochemistrymentioning
confidence: 99%